Taking care of oneself by regaining control - a key to continue living four to five decades after a suicide attempt in severe depression. Issue 1 (December 2017) - Crona, Lisa; Stenmarker, Margaretha; Öjehagen, Agneta; Hallberg, Ulrika; Brådvik, Louise
Abstract Background Depression is a strong risk factor for suicide and suicide attempt. Several studies have examined the pathway to suicide attempt, but few studies have considered aspects important for overcoming being suicidal. The aim of the present study was to examine personal strategies to continue living after a suicide attempt. Methods A qualitative grounded theory approach was used. Thirteen former inpatients diagnosed with severe depression (1956–1969) participated in a follow-up 42–56 years after their last suicide attempt, which occurred between the ages of 21 and 45. They were interviewed on one occasion between June 2013 and January 2014, using semi-structured interviews. Results The pathway to a suicide attempt was defined as 'being trapped in an overwhelming situation'. Three categories described the recovery process: 'coming under professional care', 'experiencing relief in the personal situation', and 'making a decision to continue living'. These categories emerged in a core category, labelled 'taking care of oneself by regaining control'. Overcoming being suicidal occurred regardless of recovering from depression. Conclusion In the very long-term course following a suicide attempt, the process of recovery is multi-dimensional and fluctuating, and includes appropriate treatment, connecting with others, decision making, and overcoming existential issues.